Competitive advantage in the renewable energy industry: Evidence from a gravity model. (February 2019) - Kuik, Onno; Branger, Frédéric; Quirion, Philippe
Abstract: Pioneering domestic environmental regulation may foster the creation of new eco-industries. These industries could benefit from a competitive advantage in the global market place. This article examines empirical evidence of the impact of domestic renewable energy policies on the export performance of renewable energy products (wind and solar PV). We use a gravity model of international trade with a balanced dataset of 49 (for wind) and 40 (for PV) countries covering the period 1995–2013. The stringency of renewable energy policies is proxied by installed capacities. Our econometric model shows evidence of competitive advantage positively correlated with domestic renewable energy policies, sustained in the wind industry but brief in the solar PV industry. We suggest that the reason for the dynamic difference lies in the underlying technologies involved in the two industries. Highlights: We study how RE promotion policies impact exports of wind and solar-related products. We estimate a gravity model to explain international trade in RE-related products. Our data comprise 49 (wind) and 40 (solar PV) countries for the period 1995–2013. We show evidence of policy-induced competitive advantage in the wind and solar PV industries. Competitive advantage is sustained in the wind industry but brief in the solar PV industry.